Effect of high-risk sleep apnea on treatment-response to a tailored digital cognitive behavioral therapy for insomnia program: a quasi-experimental trial - Sweetman, Alexander; Reynolds, Chelsea; Lack, Leon; Vakulin, Andrew; Chai-Coetzer, Ching Li; Wallace, Douglas M.; Crawford, Megan; Richardson, Cele (Frontiers in Sleep, 2024)
Introduction Therapist-delivered Cognitive Behavioral Therapy for Insomnia (CBTi) is an effective but largely inaccessible treatment for people with Co-Morbid Insomnia and Sleep Apnea (COMISA). To increase CBTi access for COMISA, we aimed to develop a self-guided interactive 5-session digital CBTi program that is appropriate for people with insomnia-alone and COMISA, and compare its effectiveness between people with insomnia-alone, vs. comorbid insomnia and high-risk sleep apnea. Methods Data from 62 adults with insomnia symptoms were used. High-risk sleep apnea was defined as a score of ≥5 on the OSA50. Participants self-reported symptoms of insomnia (ISI), depression, anxiety, sleepiness (ESS), fatigue, and maladaptive sleep-related beliefs (DBAS-16) at baseline, 8-week, and 16-week follow-up. ESS scores were additionally assessed during each CBTi session. Intent-to-treat mixed models and complete-case chi2 analyses were used. Results There were more participants with insomnia-alone [n = 43, age M (sd) = 51.8 (17.0), 86.1% female] than suspected COMISA [n = 19, age = 54.0 (14.8), 73.7% female]. There were no between-group differences in baseline questionnaire data, or rates of missing follow-up data. There were no significant group by time interactions on any outcomes. Main effects of time indicated moderate-to-large and sustained improvements in insomnia (d = 3.3), depression (d = 1.2), anxiety (d = 0.6), ESS (d = 0.5), fatigue (d = 1.2), and DBAS-16 symptoms (d = 1.2) at 16-weeks. ESS scores did not increase significantly during any CBTi session. Conclusion This interactive digital CBTi program is effective in people with insomnia-alone, and people with co-morbid insomnia and high-risk sleep apnea. Further research is required to determine the effectiveness, safety and acceptability of digital CBTi in people with insomnia and confirmed sleep apnea. Clinical Trial Registration This trial was prospectively registered on the Australian and New Zealand Clinical Trials Registry (ANZCTR, ACTRN12621001395820).